Caffeoylquinic acids as inhibitors for HIV-I protease and HIV-I integrase: a molecular docking study - Serina, João C. (2020)
Caffeoylquinic acids are ubiquitous phenolic compounds with several health benefits to humans and they have been shown to be promisinganti-HIV compounds. In this work, molecular docking was used to study the inhibition of HIV-I integrase and protease using caffeoylquinic acids. It was possible to establish that the naturally occurring caffeoylquinic acids are not suitable as inhibitors for protease but are very good inhibitors for integrase. A new binding site was found for 3, 4-O-di-Caffeoylquinic acid between the chains of HIV-I integrase that could possibly lead to a disruption of the catalytic process of HIV-I integrase.